Pediatric Nonblastic Non-Hodgkin’s Lymphoma: A Perspective from India - Radhakrishnan, Venkatraman; Shoufeej, P M; Totadri, Sidharth; Ganesan, Prasanth; Ganesan, Trivadi; Sagar, Tenali (Indian Journal of Medical and Paediatric Oncology, 2018)
Background: There is a paucity of data on pediatric nonblastic non-Hodgkin's lymphoma (NHL) from developing countries. We conducted this study to study outcome and identify risk factors that can predict survival in pediatric nonblastic NHL at our center. Methods: Patients <18 years of age who were diagnosed with nonlymphoblastic NHL at our hospital from January 1, 2005, to December 31, 2014, were included. Data were collected retrospectively from case records. Results: One hundred and two patients with median age of 12 years (range: 1–18) were included in the study. There were 69/102 (68%) male and 33/102 (32%) female patients. The most common histological diagnosis was Burkitt's lymphoma (BL) in 59/102 (58%) patients followed by anaplastic large cell lymphoma (ALCL) in 28/102 (28%) patients and diffuse large B-cell lymphoma (DLBCL) in 12/102 (12%) patients, T-cell lymphoma in 2/102 patients, and primary mediastinal B-cell lymphoma in 1/102 patients. The LMB-89 protocol was the most common protocol used for treatment in 74/102 (72%) patients. The 2-year event-free survival (EFS) for patients with BL, ALCL, and DLBCL was 72%, 55.8%, and 27.5%, respectively (P = 0.037). On univariate analysis, factors that significantly predicted poor EFS included non-BL histological subtype, poor performance status, malnutrition, use of less intense chemotherapy, and not achieving complete response on interim radiological assessment. Conclusions: Outcomes in nonblastic NHL from our center are worse compared to data from the west. This is because a large proportion of patients present with advanced stage and in moribund condition. Patients with BL have better outcome compared to other subtypes.
Keywords: Chemotherapy; non-Hodgkin lymphoma; survival